(untitled) (The International Journal for Scientific Research, 2023)
The study aimed to explore the relevance between cultural beliefs and health. The study applied the social survey approach. The research population of this study was chosen from the students of the Faculty of Arts and Humanities, King Abdulaziz University in Jeddah. The study sample comprised 195 students. The questionnaire tool was used to collect data. The study reached several results, the most important of which are: the study sample members are of a high cultural level and they showed 71.5% agreement on the axis of the level of culture and its relevance to maintaining health, especially through living in a clean and healthy home in terms of good ventilation and sunshine, and following guidelines for preventing infectious diseases. Also, the results also showed a neutral response of study sample regarding the role of cultural beliefs in the diagnosis some diseases, with a total percentage of 63.1%. Through means, the items were arranged in a descending order according to the degree and percentage of agreement. The most recurrent items that refer to the role of cultural beliefs in the diagnosis of some diseases from the point of view of the sample members and achieved the highest mean and response level (Agree) are: (I do not go to the doctor except unless I have a severe illness; I depend on family experiences for treatment; and I consult my friends when I feel symptoms of illness). Moreover, the results of the study showed no statistically significant differences in the means of the sample members’ opinions regarding (the cultural level and its relevance to maintaining health) and (the role of cultural beliefs in the diagnosis of some diseases) according to the variable of age. There are statistically significant differences at the level of (0.05) in the means of the sample members’ opinions regarding (the cultural level and its relationship to maintaining health) according to the father’s level of education. There are no statistically significant differences regarding (the role of cultural beliefs in diagnosing some diseases) according to the variable of the father’s education level. There are statistically significant differences at the level of (0.05) in the means of the sample members’ opinions regarding (the cultural level and its relevance to maintaining health) according to the mother’s level of education. There are statistically significant differences at the level of (0.05) in the means of the sample members’ opinions regarding (the role of cultural beliefs in the diagnosis some diseases) according to the mother’s level of education. There are no statistically significant differences in the means of the sample members’ opinions regarding (the cultural level and its relevance to maintaining health) and (the role of cultural beliefs in the diagnosis of some diseases) according to the variable of family income level.